2019
DOI: 10.1111/dom.13666
|View full text |Cite
|
Sign up to set email alerts
|

Superior efficacy of insulin degludec/liraglutide versus insulin glargine U100 as add‐on to sodium‐glucose co‐transporter‐2 inhibitor therapy: A randomized clinical trial in people with uncontrolled type 2 diabetes

Abstract: Aim To investigate the efficacy and safety of insulin degludec/liraglutide (IDegLira) versus insulin glargine 100 units/mL (IGlar U100) as add‐on to sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor therapy. Materials and methods In this 26‐week, phase IIIb, open‐label, parallel‐group, treat‐to‐target trial, conducted at 74 sites in 11 countries, insulin‐naïve people aged ≥18 years with glycated haemoglobin (HbA1c) 53–97 mmol/mol (7.0–11.0%), body mass index 20–40 kg/m2 and inadequately controlled type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 20 publications
4
64
0
1
Order By: Relevance
“…Insulin degludec/liraglutide (IDegLira) is a fixed‐ratio soluble combination of insulin degludec (degludec) and the GLP‐1RA liraglutide (100 U and 3.6 mg/mL, respectively), which allows once‐daily administration of both active ingredients with a single injection. The efficacy and safety of IDegLira has been investigated in a number of patient populations in the DUAL clinical trial programme . Based on evidence from these trials, IDegLira received regulatory approval from the European Medicines Agency and the US Food and Drug Administration (FDA)…”
Section: Introductionmentioning
confidence: 78%
“…Insulin degludec/liraglutide (IDegLira) is a fixed‐ratio soluble combination of insulin degludec (degludec) and the GLP‐1RA liraglutide (100 U and 3.6 mg/mL, respectively), which allows once‐daily administration of both active ingredients with a single injection. The efficacy and safety of IDegLira has been investigated in a number of patient populations in the DUAL clinical trial programme . Based on evidence from these trials, IDegLira received regulatory approval from the European Medicines Agency and the US Food and Drug Administration (FDA)…”
Section: Introductionmentioning
confidence: 78%
“…IDegLira is a fixed‐ratio combination of basal insulin degludec 100 units/mL (degludec) and the glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) liraglutide (3.6 mg/mL) that is administered as a simple once‐daily injection . The safety and efficacy of IDegLira were investigated in the Dual Action of Liraglutide and Insulin Degludec in Type 2 Diabetes (DUAL) clinical trial programme …”
Section: Introductionmentioning
confidence: 99%
“…The DUAL II and DUAL IX trials assessed the safety and efficacy of IDegLira in patients with T2D treated with oral antidiabetic drug (OAD) therapy or basal insulin (DUAL II). The DUAL II trial established the distinct contribution of the liraglutide component of IDegLira by comparing IDegLira with degludec, both capped at 50 U, and the DUAL IX trial investigated IDegLira versus insulin glargine 100 units/mL (IGlar U100) added on to sodium‐glucose co‐transport protein‐2 inhibitors (SGLT2is) . Patients discontinued SUs in DUAL II or dipeptidyl peptidase‐4 inhibitors (DPP4is) in DUAL IX before starting IDegLira.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs), injectable incretin mimetics that lower fasting and post‐prandial blood glucose in a glucose‐dependent manner, provides patients who have uncontrolled T2D with basal insulin an effective intensification option that offers a lower treatment burden, a reduced risk of hypoglycaemia, and weight loss or weight maintenance as opposed to weight gain, compared with intensifying therapy with prandial insulin . Fixed ratio combination (FRC) injectable therapies with basal insulin/GLP1‐RA therapy provide these advantages and further reduce treatment burden …”
Section: Introductionmentioning
confidence: 99%
“…Results from the DUAL clinical trial programme demonstrated that the FRC IDegLira combines the benefits of the basal insulin degludec (degludec) and the GLP‐1RA, liraglutide, in a single daily injection, with a stepwise titration algorithm that contributes to attenuating the primary side effects associated with each component . The DUAL VII trial compared the efficacy and safety of IDegLira with basal–bolus therapy (insulin glargine 100 units/mL [IGlar U100] + insulin aspart [IAsp] ≤4 times daily) in patients with T2D who were inadequately controlled with basal insulin and metformin .…”
Section: Introductionmentioning
confidence: 99%